Improving Pro-Sustainable Customer Responses Through Spiritual Marketing - Khalid Kadhim Mohammed (Indonesian Journal Publisher, 2026)
The purpose of this section is to reveal the role of spiritual marketing in enhancing customers' pro-sustainability response among a sample of visitors to religious tourist sites in Karbala (the cities of Sayyid al-Awsiya and al-Za'ir). This objective stems from a key research question: